Urinary incontinence in Japanese women with chronic obstructive pulmonary disease: review - Hirayama, Fumi; Binns, Colin; Lee, Andy (The Society of Physical Therapy Science, 2005)
The relationship between urinary incontinence and chronic obstructive pulmonary disease (COPD) among Japanese women is reviewed. The prevalence of COPD is increasing because of the aging population and the high rate of cigarette consumption. The prevalence of COPD in Japan was 16.4% for males and 5% for females aged 40 years and above in 2000. COPD is a progressive disease, which can have periods of relative stability but readily regresses. Its characteristic symptoms include cough, sputum production, dysponea and frequently urinary incontinence. The persistent cough of COPD increases intra-abdominal pressure and results in increased rates of urinary incontinence especially for female patients. The prevalence of urinary incontinence among Japanese women with chronic lung disease varied between 30.4% and 68%, which was comparatively higher than those of the general population (25-56.9%) and outpatient clients attending gynaecology clinics (27-31%). However, there is no published report specifically on the prevalence of urinary incontinence for Japanese women with COPD. As COPD is one of the causes of urinary incontinence, the obvious prevention strategy is tobacco control and early detection using screening test. Urinary incontinence should be identified and dealt with in order to improve the quality of life for COPD patients.